Seven Steps of Interreligious Dialogue of Action Increasing Employee's Engagement - Kanisius Komsiah Dadi; Theresia Maria Margi Jatining Kasih (Fakultas Teologi, Universitas Sanata Dharma, 2024)
The present study aims to identify an effective way of promoting employee engagement through interfaith dialogue. The research employed a descriptive qualitative approach, and the sample consisted of Atma Jaya Catholic University of Indonesia employees. As a Catholic institution, Atma Jaya is committed to the values of the Christian faith and Pancasila (Tuhan dan Tanah Air), which reflect Indonesia's diverse cultural and religious landscape. The university's founders envisioned an academic community embodying Christian faith, excellence, professionalism, and care (Kristiani, Unggul, Profesional, Peduli-KUPP). However, building these values in every community member has proven to be a challenge, as evidenced by the low level of employee engagement.Employee engagement is an essential factor in promoting individual well-being and organizational success. It refers to the positive, fulfilling, and meaningful involvement in work activities characterized by dedication, enthusiasm, and absorption. Work plays a critical role in societal development, as it contributes to advancing various fields and providing goods and services. In this regard, Atma Jaya can leverage dialogical approaches to enhance the quality of social life in society. The university has adopted a strategy for promoting dialogue among individuals from diverse ethnic, religious, and cultural backgrounds, known as